SERPIH PEMIKIRAN JEAN JACQUES ROUSSEAU TERHADAP PENDIDIKAN - Rahmadi Rahmadi; Rusma Yulidawati (STIT Darul Hijrah Martapura, 2021)
This research aims to investigate Jean Jacques Rousseau's thoughts on education and its implications in modern educational practices. Rousseau advocated for an education that emphasizes freedom, authenticity, and the natural happiness of human beings. The research method used is the analysis of Rousseau's primary texts, such as